2017
DOI: 10.3389/fnint.2017.00006
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Video Pupillography Coupled with Smart Phone LED for Measurement of Pupillary Light Reflex

Abstract: Clinical assessment of pupil appearance and pupillary light reflex (PLR) may inform us the integrity of the autonomic nervous system (ANS). Current clinical pupil assessment is limited to qualitative examination, and relies on clinical judgment. Infrared (IR) video pupillography combined with image processing software offer the possibility of recording quantitative parameters. In this study we describe an IR video pupillography set-up intended for human and animal testing. As part of the validation, resting pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Kasthurirangan and Glasser studied the dynamic accommodative and pupillary responses to step stimuli in 66 human subjects (ages: 14–45 years) and demonstrated that the mean peak velocity of pupil constriction decreases significantly with age. The pupillary dynamics were also studied in guinea pigs, using a protocol that allows quantitative evaluation of the constriction and re‐dilation response over time . It was found that the constriction and re‐dilation velocity significantly decrease in adult guinea pigs compared with juvenile ones .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kasthurirangan and Glasser studied the dynamic accommodative and pupillary responses to step stimuli in 66 human subjects (ages: 14–45 years) and demonstrated that the mean peak velocity of pupil constriction decreases significantly with age. The pupillary dynamics were also studied in guinea pigs, using a protocol that allows quantitative evaluation of the constriction and re‐dilation response over time . It was found that the constriction and re‐dilation velocity significantly decrease in adult guinea pigs compared with juvenile ones .…”
Section: Discussionmentioning
confidence: 99%
“…The pupillary dynamics were also studied in guinea pigs, using a protocol that allows quantitative evaluation of the constriction and re‐dilation response over time . It was found that the constriction and re‐dilation velocity significantly decrease in adult guinea pigs compared with juvenile ones . On the other hand, Bremner has investigated the correlations between the amplitude and peak velocity of constriction in the PLR of normal subjects to determine the effects of stimulus intensity, pupil size and age on this relationship.…”
Section: Discussionmentioning
confidence: 99%
“… 54 Another study reported that reduced pupillary dilatation amplitude was detected in hyperglycemic patients with DR, 55 which may assist in patient diagnosis and stratification by severity. Smartphone LEDs have been used as stimuli in combination with infrared video pupillometry, 56 and now entirely iPhone-based pupillometry can provide similar results to infrared pupillometry. 57 Further studies are required to determine the relative accuracy, costs, and ease of these pupillary light response tests, or a combination thereof, for sensitivity and specificity for diagnosing DR and determining its severity.…”
Section: Other Diagnostic Tools For Drmentioning
confidence: 99%
“…Preliminary studies have shown comparable results between these smartphone applications and traditional infrared pupillometry. 28,29…”
Section: Advantages and Limitations Of Quantitative Pupillometrymentioning
confidence: 99%